Deregulated MicroRNA-21 Expression in Monocytes from HIV-Infected Patients Contributes to Elevated IP-10 Secretion in HIV Infection - Wu, Xian; Zhang, Le-Le; Yin, Lin-Bo; Fu, Ya-Jing; Jiang, Yong-Jun; Ding, Hai-Bo; Chu, Zhen-Xing; Shang, Hong; Zhang, Zi-Ning (Frontiers in Immunology, 2017)
Persistent activation and inflammation impair immune response and trigger disease progression in HIV infection. Emerging evidence supports the supposition that excessive production of interferon-inducible protein 10 (IP-10), a critical inflammatory cytokine, leads to immune dysfunction and disease progression in HIV infection. In this study, we sought to elucidate the cause of the upregulated production of IP-10 in HIV infection and explore the underlying mechanisms. Bolstering miR-21 levels using mimics resulted in the obvious suppression of lipopolysaccharide (LPS)-induced IP-10 in monocyte leukemia cells THP-1 and vice versa. The analysis of the primary monocytes of HIV patients revealed significantly less miR-21 than in healthy controls; this was opposite to the tendency of IP-10 levels in plasma. The secretion of IP-10 due to LPS stimulation was not affected by miR-21 modulation in the differentiated THP 1 macrophages (THP-1-MA). We found a novel switch, IFN stimulated gene 15 (ISG15), which triggers the expression of IP-10 and is significantly upregulated during the differentiation of THP-1 into THP-1-MA. The inhibition of ISG15 can restore the regulation of IP-10 by miR-21. In summary, IP-10 expression in monocytes is regulated by miR-21, whereas in macrophages, this fine-tuning is attenuated by the enhanced expression of ISG15. This study paves the way to a comprehensive understanding of the molecular regulatory mechanism of IP-10, a key point in immune intervention strategy.